INTEGRASI PORTAL DAN E-REGISTRASI PELATIHAN APARATUR DESA INDONESIA BAGIAN TIMUR PADA BBPD MALANG BERBASIS RAD: INTEGRATION OF THE PORTAL AND E-REGISTRATION FOR VILLAGE APPARATUS TRAINING IN EASTERN INDONESIA AT BBPD MALANG BASED ON RAD - Mochamad Agung Setiawan; Wildan Suharso (LPPM Universitas Abdurrab, 2026)
The Center for Village Government (BBPD) in Malang faces administrative challenges in training village officials across 16 provinces in Eastern Indonesia. This study aims to design and implement a web-based integrated portal and E-Registration system to solve the inefficiencies of manual data management across regions. The system was developed using the Rapid Application Development (RAD) method, integrating the WordPress CMS as a public information portal and the Laravel framework as the core registration system. Key functionalities include online registration, QR Code-integrated attendance, structured regional hierarchy management, and E-Certificates. System testing was conducted through Blackbox Testing, performance testing, quantitative efficiency evaluation, and the System Usability Scale (SUS). Test results indicate that this integrated system functions stably with an average response time of under 3 seconds. Quantitatively, the integrated system successfully increased verification time efficiency by 65%, reduced data input errors (human error) from 15% to under 3%, and accelerated certificate distribution from a 4-day queue to under 1 minute. A SUS score of 84.5 (Excellent) proves the system interface is highly user-friendly for village officials with diverse digital literacy backgrounds. In conclusion, the integration of these two platforms has successfully achieved an efficient, transparent, and inclusive e-government administrative transformation within BBPD Malang.